1984
DOI: 10.1149/1.2115959
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Doped Iron Oxide Electrodes for the Photodissociation of Water: Stability, Optical, and Electronic Properties

Abstract: A characterization of optical and electronic properties is presented for p‐type (Mg‐doped) and n‐type (Si‐doped) iron oxides used in the photoelectrolysis of water. Photocurrent vs. wavelength spectra for these electrodes indicate that α‐Fe2O3 is the active optical component for both p‐type and n‐type materials. Band‐edge locations for p‐type and n‐type iron oxides in sodium hydroxide aqueous solution are determined from differential capacitance measurements. The thermodynamic feasibility of the catalytic pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 19 publications
4
61
0
Order By: Relevance
“…Typically, the capacitance is determined by fitting the frequency responses with a simple resistor-capacitor (RC) circuit model (see Figure 8 a). A single frequency, [30,50,56] multiple frequencies, [105] extrapolating to an infinite frequency, [54,57,126] or an entire range of high frequencies [65,[127][128] (for heavily doped samples) have been reported for both planar and structured electrodes. [24,[127][128] However since the classic MS relation relies on a simple parallel-plate capacitor model the application of EIS data from real systems has often been problematic.…”
Section: Advanced Understanding By Using Electrochemical Impedance Spmentioning
confidence: 99%
“…Typically, the capacitance is determined by fitting the frequency responses with a simple resistor-capacitor (RC) circuit model (see Figure 8 a). A single frequency, [30,50,56] multiple frequencies, [105] extrapolating to an infinite frequency, [54,57,126] or an entire range of high frequencies [65,[127][128] (for heavily doped samples) have been reported for both planar and structured electrodes. [24,[127][128] However since the classic MS relation relies on a simple parallel-plate capacitor model the application of EIS data from real systems has often been problematic.…”
Section: Advanced Understanding By Using Electrochemical Impedance Spmentioning
confidence: 99%
“…Hematite, α-Fe 2 O 3 , has a much more favorable 2.2 eV band gap for solar harvesting and therefore absorbs about 40% of the air mass 1.5 solar spectrum [6][7][8]. Previous researchers found that the energetic position of the valence band edge in hematite is appropriate for water oxidation [9][10][11][12][13][14][15][16][17][18][19][20][21]. In fact, iron oxides are amongst the smallest band gap semiconductors that are stable toward oxygen evolution and are certainly the least expensive of them.…”
Section: Introductionmentioning
confidence: 99%
“…They found the acceptor density to be 4.41 Â 10 17 and 5.57 Â 10 17 cm À3 at frequencies of 791 and 250 Hz, respectively. The acceptor densities obtained for Cu- [37], Zn- [36] and Mg-doped [6] a-Fe 2 O 3 are 2-3 orders of magnitude lower than for undoped n-Fe 2 O 3 [35]. These lower acceptor densities may be responsible for the lower photocurrent density obtained for p-type a-Fe 2 O 3 samples.…”
Section: Flatband Potential and Donor Densitymentioning
confidence: 83%
“…Doping of Mg 2 þ and Zn 2 þ in a-Fe 2 O 3 has been found to exhibit some peculiar characteristics related to p-type behavior [6,28]. These electrodes exhibited the phenomenon of transformation from negative to positive photocurrent, when the external potential was varied from negative to positive.…”
Section: Bivalent Metal-ion Doping: P-type A-fe 2 Omentioning
confidence: 99%
See 1 more Smart Citation